Survival and success of tooth-implant-supported and solely implant-supported double-crown-retained overdentures: a prospective study over a period of up to 11 years - Klotz, Anna-Luisa; Fobbe, Hannah; Rammelsberg, Peter; Lorenzo Bermejo, Justo; Kappel, Stefanie (Clinical oral implants research, 2021)
Objectives To investigate the long-term performance, over a period of up to 11 years, of tooth-implant-supported and solely implant-supported double-crown-retained overdentures (DCRDs) for complete restoration of the jaw. Materials and methods Between 2002 and 2015, patients were consecutively enrolled in the study at Heidelberg University Hospital's Department of Prosthodontics. Scheduled and unscheduled visits were both documented on standardized forms. Kaplan-Meier curves were used to evaluate survival and success of the DCRDs. Mixed effects Cox regression was used to identify the potential effects of age, sex, jaw, location of implants, and the number of abutment teeth on the success of the DCRDs. Results One hundred and thirty-nine DCRDs were placed in 126 participants (mean age: 65.6 ± 9.1 years; 76 [60.3%] men). The mean follow-up period was 4.2 years. Fifty-three (38%) DCRDs were solely implant-supported (213 implants) and 86 (62%) were tooth-implant-supported (239 teeth and 199 implants). Cumulative five-year survival was 96.2% in the implant-supported group and 97.7% in the tooth-implant-supported group. Simultaneous consideration of failures and severe complications revealed cumulative five-year success of 88.2% for implant-supported DCRDs and 81.9% for tooth-implant-supported DCRDs, with no significant difference between the two types of restoration. Cox regression analysis revealed a greater risk of major complications (hazard ratio: 4.87, p = .04) for maxillary DCRDs than for mandibular DCRDs. Conclusions Although the study design has limitations, the results show that tooth-implant-supported and solely implant-supported DCRDs are both recommendable treatment options. After a mean follow-up of 4.2 years, survival and success were high. However, minor complications were common and required much aftercare. Clinical Trial Registration This study started in 2005 and was approved by the local review board of the University of Heidelberg. In 2005, clinical trial registration was not yet common. For this reason, the study was not registered.